Modulation of gut microbiota and immune response by soy peptides mitigates irinotecan induced intestinal toxicity - Jing, Yongfa; Yan, Dongli (Frontiers in Physiology, 2025)
IntroductionIrinotecan (CPT-11), a cornerstone chemotherapeutic agent for colorectal and pancreatic cancers, is limited by severe gastrointestinal toxicities, particularly diarrhea, which compromises treatment adherence and patient quality of life. Soy peptides (SPs), bioactive compounds with anti-inflammatory and prebiotic properties, have shown potential in enhancing intestinal barrier function. This study investigates SPs’ protective effects against irinotecan-induced intestinal injury, focusing on microbiota modulation, immune regulation, and mucosal repair.MethodsFemale C57BL/6 mice were randomly divided into four groups (n = 10/group): Control, Irinotecan, Pre-SPs+ Irinotecan, and SPs+ Irinotecan. Diarrhea severity and body weight changes were monitored daily. Small intestinal injury was evaluated by hematoxylin and eosin (H&E) staining with epithelial damage scoring, while intestinal barrier integrity was assessed via Western blotting (WB) and immunohistochemistry. Serum levels of inflammatory cytokines (TNF-α and IL-6) were quantified using ELISA, and neutrophil infiltration was measured by flow cytometry. Fecal samples were subjected to 16S rRNA sequencing to analyze gut microbiota composition.ResultsSPs intervention significantly reduced the incidence of diarrhea (P < 0.05) and attenuated body weight loss (P < 0.05) in mice. Histological analysis demonstrated that SPs restored intestinal architecture, as evidenced by reduced epithelial damage scores (P < 0.05), increased expression of tight junction proteins (occludin and ZO-1), and improved intestinal permeability (P < 0.05). Gut microbiota profiling revealed that irinotecan-induced dysbiosis was characterized by decreased α-diversity and enrichment of pathogenic taxa. SPs treatment restored microbial diversity and significantly elevated the abundance of beneficial genera, including Lactobacillus and Bifidobacterium (P < 0.05). Immunological assays further indicated that SPs suppressed pro-inflammatory cytokine levels (TNF-α and IL-6, P < 0.001) and reduced neutrophil infiltration (P < 0.05).DiscussionThese findings suggest that soy peptides protect against irinotecan-induced intestinal toxicity through multiple mechanisms, including microbiota regulation, immune modulation, and intestinal barrier restoration, highlighting their potential as a therapeutic candidate for chemotherapy-induced intestinal damage.